Stamtræer og digitale etymologiske ordbøger - Vrieland, Seán D (Nordiske Studier i Leksikografi, 2018)
Presentation of etymological information in dictionaries varies widely, making it difficult to propose a standard form of encoding this information in the process of digitization. The following proposes an extension of the TEI P5 standard for encoding texts using XML, wherein a new element <etymon> is able to nest recursively, thereby allowing the XML format to match that of a language family tree. Problems of reconstructed proto-forms, loanwords, and language grouping are further discussed.